Preparation of RGD Peptide/Folate Acid Double-Targeted Mesoporous Silica Nanoparticles and Its Application in Human Breast Cancer MCF-7 Cells - Yan, Huijie; You, Yun; Li, Xinjian; Liu, Lei; Guo, Fengqian; Zhang, Qiongling; Liu, Dewen; Tong, Yan; Ding, Shilan; Wang, Jinyu (Frontiers in Pharmacology, 2020)
Pharmacological relevance: Paclitaxel (PTX) is currently the only botanical drug that can control the growth of cancer cells. Paclitaxel is widely used in the treatment of breast cancer, ovarian cancer, uterine cancer, non-small cell lung cancer and other cancers. Aim: Folate receptor and integrin αvβ3 are highly expressed on the surface of human breast cancer cells MCF-7. Folic acid and arginine-glycine-aspartate (Arg-Gly-Asp, RGD) tripeptide sequence have a high affinity for folate receptor and integrin αvβ3, respectively. To enhance the effect on breast cancer, we constructed the folate acid and RGD peptide dual-targeted (MSNs-NH2-FA-RGD) drug-carrier based on mesoporous silica nanoparticles. Methods: The structure of mesoporous nanocarriers was characterized by Fourier transform infrared spectroscopy, nitrogen adsorption-desorption analysis, transmission electron microscopy, laser particle size analyzer, and thermogravimetric analysis. Paclitaxel was chosen as the model drug. The targeting-ability was verified by observing the uptake of mesoporous carriers loaded with rhodamine in MCF-7, MCF-10A, and HeLa cells using a fluorescence microscope. The cytotoxicity of the blank carrier MSNs-NH2-FA-RGD and the efficacy of the drug carrier PTX@MSNs-NH2-FA-RGD were assessed by cell experiments. Results: The characterization showed successful construction of a dual-targeted mesoporous silica nanocarrier. Obvious differences were detected in the fluorescence intensity of the three cell lines. The results of the pharmacological tests indicated that the blank nanoparticles do not cause any apparent toxicity on these cells. The IC50 of free PTX and PTX@MSNs-NH2-FA-RGD on MCF-7 cells line treated for 48 h were 35.25±2.57 ng•mL-1 and 22.21±3.4 ng•mL-1 respectively, which indicated that the inhibitory efficacy of PTX@MSNs-NH2-FA-RGD on MCF-7 was 1.6 times than that of free PTX. Conclusions: The dual-targeted nanocarrier MSNs-NH2-FA-RGD could target breast cancer cells, and sever as a potential candidate in future of drug development.